Penjadwalan Pemeliharaan Mesin Produksi Menggunakan Reliability Centered Maintenance - Sastriawan, Alun (Universitas Putra Indonesia YPTK Padang, 2024)
CV. ABC is a furniture business that produces home equipment which includes all items, namely chairs, tables, cupboards, beds, nightstands, wooden stairs, etc. The aim of this research was to determine maintenance scheduling for production machines, namely wood cutting machines and drilling machines, and provide suggestions for improving the maintenance scheduling of production machines, namely wood cutting machines and drilling machines, which are more effective. The advantage of the Reliability Centered Maintenance (RCM) method is that it prioritizes the main action of preventive maintenance, namely preventing and minimizing the consequences of failures that arise, so that it can increase the reliability and safety of the equipment used. Failure Modes and Effects Analysis (FMEA) is a technique for evaluating the level of reliability of a system to determine the effects of failure of the system. Based on the results of data processing and research discussion regarding production machine maintenance scheduling using RCM at CV. ABC, a conclusion can be drawn, namely, the Cutting Machine has a breakdown frequency of 26 times with the Bearing component having the most breakdown frequency, namely 8 times, the highest Risk Priority Number (RPN) calculation is Solenoid component with a value of 105, Mean Time to Failure (MTTF) calculation with a value of 111.5385 and Mean Time to Recovery (MTTR) with a value of 0.769231. The drilling machine has a breakdown frequency of 24 times with the Drill Bit component having the highest breakdown frequency, namely 6 times, the highest RPN calculation is the Drill Bit component with a value of 105, MTTF calculation with a value of 120.8333 and MTTR with a value of 0.8333.